Amphidoma parvula (Amphidomataceae), a new planktonic dinophyte from the Argentine Sea. Issue 1 (2nd January 2018) - Tillmann, Urban; Gottschling, Marc; Guinder, Valeria; Krock, Bernd
ABSTRACT: Amphidoma is an old though poorly studied thecate dinophyte that has attracted attention recently as a potential producer of azaspiracids (AZA), a group of lipophilic phycotoxins. A new species, Amphidoma parvula, sp. nov. is described from the South Atlantic shelf of Argentina. With a Kofoidean thecal plate pattern Po, cp, X, 6′, 6′′, 6C, 5S, 6′′′, 2′′′′, the cultivated strain H-1E9 (from which the type material of Am. parvula, sp. nov. was prepared) shared the characteristic plate arrangement of Amphidoma each with six apical, precingular and postcingular plates. Amphidoma parvula, sp. nov. differs from other species of Amphidoma by a characteristic combination of small size (10.7–13.6 µm in length), ovoid shape, high length ratio between epitheca and hypotheca, and small length ratio between apical and precingular plates. Other morphological details, such as the number and arrangement of sulcal plates and the fine structure of the apical pore complex support the close relationship between Amphidoma and the other known genus of Amphidomataceae, Azadinium . However, Am. parvula, sp. nov. lacks a ventral pore, a characteristically structured pore found in all contemporary electron microscopy studies of Amphidoma and Azadinium . As inferred from liquid chromatography coupled with tandem mass spectrometry, Am. parvula, sp. nov. did not produce AZA in measurable amounts. Molecular phylogenetics confirmed the systematic placement of Am. parvula, sp. nov. in Amphidoma (as sister species of Amphidoma languida ) and the Amphidomataceae. The results of this study have improved the knowledge of Amphidomataceae biodiversity.